Compudose® vs Ralgro®/Synovex-S® or Synovex-S®/Synovex-S® Reimplant programs for finishing yearling steers - S.B. Laudert; R.W. Lee (Kansas Agricultural Experiment Station Research Reports, 1987)
Three field trials were conducted with finishing yearling steers to compare the performance of cattle receiving Compudose® or Ralgro®/Synovex-S® and Synovex-S®/Synovex-S® reimplant combinations. No differences were found between Compudose and the reimplant programs in cattle daily gain, feed efficiency, or cost of gain. Compudose retention was 97.5% in the 1317 head implanted. Synovex-S implant site abscess rate ranged from 5.7 to 15.4%.
Keywords: Cattlemen' s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Compudose® vs Ralgro®; Reimplant; Steers